Tectonic Geomorphology of the Karangsambung Area, Central Java, Indonesia (Rudarsko-geološko-naftni zbornik, 2021)
Karangsambung, located in Central Java, Indonesia has complex geological conditions of the tectonic evolution of Java Island due to the subduction process of the India-Australia plate with the Eurasian plate in the Cretaceous-Paleocene. The tectonic movements in the subduction zone have resulted in diverse geological structures and rock types and impact the morphological shape of the study area. The level of tectonic activity in the study area can be determined using a tectonic geomorphological approach. A digital elevation model and geographic information systems are used for geomorphic data processing. Geological data observations were also carried out in the form of river terraces. Seven geomorphic index parameters have been calculated to determine the youngest tectonic activity through the relative tectonic activity index (IAT) of the study area: the ratio of the valley floor width to the valley height, the drainage basin asymmetry, the river gradient-length index, the basin shape index, mountain front sinuosity, drainage density, and the hypsometric integral/hypsometric curve. The IAT score is divided into four classes which are class 1 (0%) very highly, class 2 (13%) highly, class 3 (56%) moderately, and class 4 (31%) low. The IAT shows that the research area is categorized as an active tectonic area so that the morphology formed is more influenced by tectonic activity than erosion. Geological data analysis on uplifted and deformed river terrace outcrops shows that the study area is affected by neotectonic activity.